Vibration Monitoring and Damage Assessment of a Retrofitted RC Frame Model - Vimuttasoongviriya*, Atiwat; Kwatra, Naveen; Kumar, Maneek (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The need for structural damage assessment is continuously growing to monitor the damage level of existing civil structures. The information of damage assessment is utilized to make decisions on maintenance of damaged structure. This paper intends to investigate the effect of lateral load on the damage indexes of RC frame model strengthened using FRP sheets. Failure mechanism of the experimental frame model has been investigated. The effects of FRP wrap have been reported. Subsequently, the damage indexes based on modal parameters method are investigated with the help of impact hammer excitation test. Results of this study show that the use of FRP wrapped for structural retrofitting provides increased significant lateral load capacity and ductile behaviour.The damage indexes of retrofitted frame reduce indicating better performance as compare to the control frame. Keywords: Damage index, non-ductile structure, retrofitted RC frame, FRP sheet, FRF. E-mail: atiwat.vimut@gmail.com